Features ideology of Islamic radicalism in Central Asia (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the image of Islam in present time . The authors analyzed the situation and possibility of religious extremism in the Central Asian region, especially in Kazakhstan. Also considered extremist organizations such as «Hizb ut- Tahrir», «Islamic Movement of Uzbekistan», «Salafis» and others. The authors noted that the study of this issue the historical aspect completely excluded from the attention of scientists when they doing analysis of the evolution of the problem of pseudo-religious and political extremism in Central Asia, when studying the post-Soviet period. The article shows that currently Central Asia witnessed the gradual transformation of radical organizations and their merging with «al-Qaeda», and changing policies and methods of their work. In fact, we become witnesses of as «yesterday’s» organizational model of Islamic groups outlives itself, and in their place comes a new. Today apparent bet to well-trained members of the groups, which are designed to act very autonomously outside any organization, and focused guided only by general ideological attitudes. Individual singles, small cells binds only common goal, a common ideology. Key words: «Hizb ut-Tahrir», «Islamic Movement of Uzbekistan», «Salafis» Wahhabism ideology, radicalism and religious situation.